Compressive Strength, Temperature Performance and Shrinkage of Concrete Containing Metakaolin - Mansour, Mohammed A.; Ismail, Mohd Hanif; A. Majid, Masni; Md Noor, Nurazwa; Deraman, Rafikullah (International Journal of Integrated Engineering, 2023)
The influence of metakaolin (MK) on concrete was investigated as a partial replacement of cement, which is liable for high content of CO2 emission during the manufacturing process. The study aimed to assess the compressive strength, temperature performance and drying shrinkage of MK blended concrete. Different ratios of MK (5%, 10%, and 15%) as cement replacement, and two ratios of superplasticizer (SP), 1.5%, and 2% as cement weight were utilized in this study. The results indicated that using MK increased the compressive strength at 28¬ day. The improvement of strength is ascribed to the pozzolanic reaction and the packing effect of fine MK particles. MK blended concrete experienced a decrease in the temperature rise of heat of hydration (HOH) and low drying shrinkage when compared to the control concrete. The SP ratio does not have significant effect on the temperature of the concrete mixtures: however, using 1.5% SP slightly reduces the drying shrinkage of MK blended concrete compared to 2% SP. In conclusion, Incorporation of MK as partial cement substitute enhances the concrete strength, thus various types of concrete can be produced. Low temperature and drying shrinkage of MK blended concrete help in reducing thermal crack after casting process.